Aransemen Keroncong Lagu Widodari Karya Denny Caknan - Ardianwicaksono; Rizki Harmono Sejati, Irfanda (Program Studi Pendidikan Musik, 2023)
This study aims to explore and explain the process of arranging Keroncong in the song Widodari by Deny Caknan as well as the presence of local aesthetics and local wisdom in the arrangement. This study applies local theories of intelligence and musical arrangements. This study was designed using descriptive qualitative research methods as well as data collection, analysis, and conclusion procedures. The results show that Widodari's arrangement of Keroncong song contains local aesthetic elements, such as engkel musical concept, double concept and ngganduli vocal concept. In addition, the arrangement process also contains local wisdom values such as aspects of tolerance and mutual cooperation. Tolerance shows that no instrument is superior to another, everything must be in balance. Mutual cooperation is expressed through the intertwining of Keroncong instruments, which cannot work individually but complement each other.